2017
DOI: 10.1590/1414-431x20176335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 4-week high-intensity interval training on pacing during 5-km running trial

Abstract: This study analyzed the influence of a 4-week high-intensity interval training on the pacing strategy adopted by runners during a 5-km running trial. Sixteen male recreational long-distance runners were randomly assigned to a control group (CON, n=8) or a high-intensity interval training group (HIIT, n=8). The HIIT group performed high-intensity interval-training twice per week, while the CON group maintained their regular training program. Before and after the training period, the runners performed an increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
3
7
0
2
Order By: Relevance
“…In addition, when comparing the Post-2 results, the POL group decreased their RPE values compared to the HIIT group, suggesting a superior improvement in exercise tolerance after POL training compared to HIIT, despite HIIT training comprising a greater high-intensity exercise volume. These data are in accordance with previous works comparing HIIT against lower intensity exercise modalities ( Astorino et al, 2016 ; Silva et al, 2017 ), showing that HIIT training does not reduce RPE during a moderate-intensity exercise. Thus, POL training seems to be more efficient at improving exercise tolerance in untrained overweight women.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, when comparing the Post-2 results, the POL group decreased their RPE values compared to the HIIT group, suggesting a superior improvement in exercise tolerance after POL training compared to HIIT, despite HIIT training comprising a greater high-intensity exercise volume. These data are in accordance with previous works comparing HIIT against lower intensity exercise modalities ( Astorino et al, 2016 ; Silva et al, 2017 ), showing that HIIT training does not reduce RPE during a moderate-intensity exercise. Thus, POL training seems to be more efficient at improving exercise tolerance in untrained overweight women.…”
Section: Discussionsupporting
confidence: 93%
“…The major findings of this investigation were that a 4-week HIIT program with a total of 12 training sessions is able to improve vmax during a progressive incremental exercise test as well as v O 2 max and AT. This confirms the findings of other research studies that have demonstrated that a HIIT program performed during 4 weeks is an effective short-term strategy to alter some variables related to endurance performance in well-trained athletes ( Laursen et al, 2005 ; Driller et al, 2009 ; Lamberts et al, 2009 ; Swart et al, 2009 ; Silva et al, 2017 ). Furthermore, the collected data showed that ACT did not attenuate training adaptations during the mesocycle compared to PAS.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been proposed that endurance performance is also influenced by running economy, which in turn is a concept that reflects the integrated composite not only of metabolic and cardiorespiratory capacities (i.e., substrate utilization, O 2 max) but also of biomechanical and neuromuscular characteristics (i.e., running style, motor programming; Barnes and Kilding, 2015 ). In this context, Silva et al (2017) revealed that a 4-week HIIT mesocycle in fact improved running economy. An increase in running economy could lead to a lower energy cost during submaximal running bouts, which might also allow the athletes to achieve higher speeds at the end of the maximal incremental treadmill test ( Silva et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this could not be the case, especially at high loads, if other performance variables, such as running economy, were improved. Silva et al (2017) reported that a HIIT program mediates a reduction in the energetic cost of running, allowing runners to achieve higher speeds at the end of the maximal incremental treadmill test without significant increases in the VO 2 max. There is also some evidence that improvements in high-intensity aerobic performance are not strongly associated with improvements in VO 2 max since low responders for one parameter are not necessarily low responders for another (Vollaard et al, 2009).…”
Section: Discussionmentioning
confidence: 99%